New record of the genus Bambusiphaga (Hemiptera: Delphacidae: Tropidocephalini) from India with description of a new species - N., Ramya.; Meshram, Naresh M. (Zootaxa, 2019)
The genus Bambusiphaga Huang & Ding is recorded from India for the first time and one new species B. unispina sp. nov. is described and illustrated. The new species is similar to B. taiwanensis (Muir) but can be separated by the male genitalic structure.